ANDROID APPLICATION FOR DETECTION OF SKIN CANCER USING EXPERT SYSTEM - Udjaja, Yogi (Social Economics and Ecology International Journal, 2018)
Skin cancer is an abnormal growth of human skin that can damage skin cells. By knowing the symptoms of skin cancer as early as posssible, it is helpful in preventing the spread of cancer cells and treatment. There are many factors that cause skin cancer, but in general the cause is exposure to ultraviolet rays from the sun. Therefore, an expert system application is required to detectskin cancer. By using backward chining and probalility methode; which data is in form of someone’s risk factor and clinical sympthoms, then the application will provide temporary diagnosis. This application is built in an android platfrom because in its development android is more used than other platforms. The accuracy obtained from this application is 96.67%.